Healthcare professionals' knowledge on cardiopulmonary resuscitation correlated with return of spontaneous circulation rates after in-hospital cardiac arrests: A multicentric study between university hospitals in 12 European countries. (1st June 2020) - Kourek, Christos; Greif, Robert; Georgiopoulos, Georgios; Castrén, Maaret; Böttiger, Bernd; Mongardon, Nicolas; Hinkelbein, Jochen; Carmona-Jiménez, Francesc; Scapigliati, Andrea; Marchel, Michal; Bárczy, György; Van de Velde, Marc; et al.
Abstract: Background: In-hospital cardiac arrest is a major cause of death in European countries, and survival of patients remains low ranging from 20% to 25%. Aims: The purpose of this study was to assess healthcare professionals' knowledge on cardiopulmonary resuscitation among university hospitals in 12 European countries and correlate it with the return of spontaneous circulation rates of their patients after in-hospital cardiac arrest. Methods and results: A total of 570 healthcare professionals from cardiology, anaesthesiology and intensive care medicine departments of European university hospitals in Italy, Poland, Hungary, Belgium, Spain, Slovakia, Germany, Finland, The Netherlands, Switzerland, France and Greece completed a questionnaire. The questionnaire consisted of 12 questions based on epidemiology data and cardiopulmonary resuscitation training and 26 multiple choice questions on cardiopulmonary resuscitation knowledge. Hospitals in Switzerland scored highest on basic life support ( P =0.005) while Belgium hospitals scored highest on advanced life support ( P <0.001) and total score in cardiopulmonary resuscitation knowledge ( P =0.01). The Swiss hospitals scored highest in cardiopulmonary resuscitation training ( P <0.001). Correlation between cardiopulmonary resuscitation knowledge and return of spontaneous circulation rates of patients with in-hospital cardiac arrest demonstrated that each additional correct answer on the advanced life support score results in a further increase in return of spontaneous circulation rates (odds ratio 3.94; 95% confidence interval 2.78 to 5.57; P <0.001). Conclusion: Differences in knowledge about resuscitation and course attendance were found between university hospitals in 12 European countries. Education in cardiopulmonary resuscitation is considered to be vital for patients' return of spontaneous circulation rates after in-hospital cardiac arrest. A higher level of knowledge in advanced life support results in higher return of spontaneous circulation rates.